Kubernetes Operators : Revolutionizing Application Management and Automation - Praneel Madabushini, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and impact of Kubernetes Operators in modern cloud-native computing environments. The article examines how operators extend Kubernetes' native capabilities through control loops and automated management, highlighting their crucial role in streamlining operations across database management, machine learning workflows, and security compliance. The article investigates implementation challenges, including technical prerequisites and operational complexities faced by organizations adopting Operator-driven solutions. Additionally, it explores future prospects, particularly focusing on AI-enhanced operations and improved development tools, while providing insights into market trends and technological advancements that will shape the future of container orchestration and application management.
Keywords: Kubernetes Operators; Cloud-Native Computing; Container Orchestration; Automated Operations